Democracy and Income In-Equality: An Empirical Analysis - Mark Gradstein; Branko Milanovic; Yvonne Ying (Center for Economic Studies and ifo Institute (CESifo), 2001)
While standard political economy theories suggest a moderating effect of democratization on income inequality, empirical literature has failed to uncover any such robust relationship. Here we take yet another look at this issue arguing first, that prevailing ideology may be an important determinant of inequality and, second, that the democratization effect works through ideology. In societies where equality is highly valued there is less of a distributional conflict across income groups, hence democratization may have only a negligible effect on inequality. On the other hand, in societies where equality is not valued as much, democratization reduces inequality through redistribution as the poor outvote the rich. Our cross-country empirical analysis, covering the period 1960-98 and 126 countries, confirms the hypothesis: ideology - as proxied by a country's dominant religion - seems to be related to inequality. But in addition, in Judeo-Christian societies increased democratization appears to lead to lower inequality, while in Muslim and Confucian societies democratization has only an insignificant effect on inequality. We hypothesize that in the latter group of countries, desired level of inequality is reached through informal transfers, while in Judeo-Christian societies where family ties are weaker, desired outcome is achieved by political action.
Keywords: 330; Inequality; democracy; religion